Soil fauna community diversity and response to wetland degradation in Nanniwan Wetland, Shaanxi, China - Liu, Changhai; Shao, Ying; Cao, Siping (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study is to investigate the soil fauna community characteristics in the Nanniwan wetland, as well as their responses to changed environmental factors. Soil fauna from six representative habitats in the Nanniwan wetland were studied, in the spring, summer, autumn, and winter of 2016. Soil fauna community composition, density, and distribution were investigated. The relationships between soil fauna distribution and soil physicochemical properties were also analyzed. Overall, 3285 individuals were harvested, which belonged to 4 phyla, 10 classes, and 26 orders. The soil fauna density and group numbers differed among these habitats. The structure of the reclaimed wetland soil fauna community was the simplest among all these habitats. Wetland reclamation and degradation reduced the density and diversity of soil fauna, and changed the functional groups of soil fauna, resulting in decreased saprozoic soil fauna and increased predacity soil fauna. The total organic carbon content and the soil pH value represented the main influencing factors of soil fauna distribution. The soil fauna density was positively correlated with the soil total organic carbon and total nitrogen contents, while the soil fauna density was negatively correlated with the pH value. The soil fauna density is closely associated with the environmental factors in the Nanniwan wetland. These findings would help to quantitatively predict and evaluate the ecological function of soil fauna in the Nanniwan wetland.